Blackout – Crisis Management Solution for a Large-scale Power Outage in Slovakia - Ondrej Blažek; Krzysztof Rogowski; Jacek Dworzecki (Communications of International Proceedings, 2021)
The authors focus on the issue of accidents in the electricity system and especially on ways to solve such an accident in the current conditions in the territory of the Slovak Republic. The authors strive not only to acquaint the reader about the functioning and basic principles of emergency power supply, in case of restoration of electricity supply after blackout, but based on scientific methods recommended the authors particularly examine, determine and propose crisis management procedure for emergency power supply using local power plants, and in practice can be relevant for the members of the Fire and Rescue Service as well as employees of crisis management or civil protection.
Keywords: Electricity; Power Plant; Emergency; Crisis Management; Civil Protection; Emergency Power Supply; Blackout; Accidents; Incident.